Finansman kaynağı olarak spor sponsorluğu - Çotuk, Müfide Yoruç (My University, 2007)
Bu araştırmada, bireysel sporcu ve kulüplerin spor sponsorluğu yoluyla elde etmiş olduğu kazanımları (özellikle finansman açısından) incelemek, bunun yanında kurumların bireysel ve kulüp sponsorluklarına yönelmedeki genel ve özel amaçlarını belirlemek amaçlanmıştır. Araştırmada yarı yapılandırılmış görüşme tekniği ile spor sponsorluğu konusunda uzmanlaşmış beş kişiyle yüz yüze görüşme yapılarak, nicel araştırmada kullanılacak ve ankete dahil edilecek sorular belirlenmiştir. Bu şekilde geliştirilen anket iki gruba uygulanmıştır: 1. Bireysel sponsorlukları bulunan sporcular (29 sporcu) 2. Kulüpleri adına sponsorlukları bulunan 2006–2007 sezonu Türkiye Bayanlar ve Erkekler Basketbol ve Voleybol Birinci Liglerinde yer alan kulüpler (27 kulüp) Sonuç olarak araştırmamız, bireysel sporcu ve kulüp sponsorluklarının gruba ait özellikleri dışında benzer uygulamalar ve sıkıntılar içinde olduğunu ortaya koymaktadır. Sporcuların aldıkları destekler; ulusal ve uluslararası yarışmalara katılım, maddi ve masrafların karşılanması yönündedir. Kulüpler firmalardan genellikle, maddi, aynî, isim hakkı, ulusal ve uluslararası yarışmalarda destek, masrafların karşılanması ve sağlık yardımı desteklerini almaktadırlar. Ancak bireysel sporculara ve kulüplere sunulan maddi desteğin yetersiz oluşunun yanı sıra, ülkedeki sportif anlayış şekli de bu desteklerin artmasına engel olmaktadır. Firmalarla (sponsor eden), bireysel sporcu ve kulüplerin (sponsor edilenler) arasında sponsorluk uygulamaları ile ilgili yaklaşımlarında büyük farklılıklar vardır. Bu nedenle, Türkiye’deki spor sponsorluğu uygulamaları içinde bireysel ve kulüp sponsorluklarının yerinin belirlenmesi, uygulamadaki değişkenlerin azaltılması ile spor sponsorluğunun gelişmesi ve daha etkin uygulamalara gidilebilmesi için tüm sportif alanları kapsayacak yasal uygulamalar getirilmelidir. Bu bağlamda; 1. Firmaları spora daha fazla yatırım yapmaya yöneltecek ve yeterli düzeyde vergi teşviklerinin yaratılması sağlanmalıdır. 2. Kurumsal yapıyı geliştirmek için kulüplerin dernekler kanununa bağımlı olmaları sonlandırılmalıdır. 3. Sporcuların ve kulüplerin gelirleri içinde önemli yer tutan sponsorluk gelirleri arttırılmadır. 4. Amatör sporculuk yaşantısı profesyonel hale getirilmelidir. Anahtar Kelime: Spor sponsorluğu, finansman kaynağı, bireysel sporcu sponsorluğu, kulüp sponsorluğu, pazarlama iletişimi.

SPORT SPONSORSHIP as a FINANCIAL RESOURCE The aim of this study was to identify the benefits (especially the financial ones) of sport sponsorship contracts for individual athletes and sport clubs. A further aim was to evaluate the general and specific motives of corporate organizations for the establishment of a sport sponsorship relation with the individual athletes and sport clubs. A semi structured face to face interview technique was applied to five specialists of sport sponsorship in order to identify relevant items for the questionnaire which was used for the quantitative evaluation. That questionnaire was applied to the following groups: 1. Individual athletes with sport sponsorships (29 athletes) 2. Sport clubs with sport sponsorships Turkish First Division Basketball and Volleyball Leagues (Men and Women) (27 clubs), The results of this study show that, besides group related differences of sport sponsorship for individual athletes and sport clubs, both groups struggle with similar procedures and difficulties. The athletes are supported financially for participating in the national and international events, and related revenues. The clubs are supported financially by the sponsors for participating in the national and international events, health related expenses, name rights and related revenues. But the financial support both for individual athletes and sport clubs, remain inappropriate, due to the inadequate perception of sport in the country which hinders the increase of sport sponsorship support. There are substantial divergences in the concept and application of sport sponsorship between the corporate organizations (the sponsors) and individual athletes and sponsored sport clubs both. In order to develop and determine the status of sport sponsorship of individual athletes and sport clubs in Turkey, to redaction of variance in sport sponsorship procedures and increase of the effectiveness of sport sponsorship legal and administrative steps covering all sport activities should be taken. In this context, 1. Adequate tax reductions should be implemented in order to motivate sponsors for their investments in sport and sport sponsorship, 2. In order to develop the institutionalization structure of sports clubs, dependence to the “Law of Associations” should be eliminated and special law pertaining to the sports clubs should be formalized., 3. Financial support by sport sponsors for individual athletes and sport clubs has to be increased, and 4. Inadequate living conditions of sportsmen and women should be improved to the professional quality level by way of sports sponsors. Key Words: Sport sponsorship, financial resources, individual athlete sponsorship, club sponsorship, communication marketing.
Keywords: Beden Eğitimi ve Spor; Spor